THE IMPACT OF DEPRESSION SYMTOMS ON MATERNAL INCREASING THE INCIDENCE OF LOW BIRTH WEIGHT (LBW) BABIES - Handayani, Ida Farida; Pertiwi, Rahayu; Sugiarsih, Ugi (Poltekkes Kemenkes Bandung, 2025)
Maternal mental health is a critical public health concern, with around 10% of pregnant women experiencing mental disorders, particularly depression. Depression during pregnancy can negatively impact birth outcomes, including increasing the risk of Low Birth Weight (LBW). The purpose of this study was to determine the impact of maternal depression symptoms on the increase in the incidence of LBW in Karawang Regency in 2023. The research used an analytical retrospective design with data collected through questionnaires and the Edinburgh Postnatal Depression Scale (EPDS). The study population consisted of postpartum mothers, with 21 respondents in the LBW case group and 63 in the non-LBW control group. Sampling was conducted using a non-probability consecutive sampling method. Data were analyzed using the chi-square test, odds ratio (OR), and 95% confidence interval (CI), with a significance level of p < 0.05. Results showed that 22.6% of respondents experienced depressive symptoms, which were more prevalent in the case group (57.1%) than in the control group (11.1%). Depression during pregnancy was significantly associated with LBW (p = 0.0001; OR = 10.66), indicating that mothers with depressive symptoms had a 10.66 times higher risk of giving birth to LBW infants. It is recommended to strengthen counseling and education for pregnant and premarital women on reproductive health and LBW risk factors.